Zinc negative electrodes with carbon-supported metal monatomic functional coatings, their preparation and use thereof
Patent Information
- Application Number
- CN202310985640.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-08-07
AI Technical Summary
[0004]由于现有技术存在上述缺陷,本发明提供了一种利于锌的定向沉积/剥离的锌负极材料即性能好的锌负极材料,具体为一种具有氮掺杂碳负载的原子级Sn位点涂层的锌负极材料、其制备方法及其在水系锌离子电池、锌-空气电池、锌基液流电池等领域的应用,克服了现有锌负极用涂层材料不利于锌的定向沉积/剥离的缺陷
[0038](1)本发明的具有碳载金属单原子功能涂层的锌负极,通过在锌负极表面负载一层疏水、亲锌的三维功能涂层,能够引导锌离子的高速扩散,同时能够有效抑制析氢副反应,原子级亲锌位点和三维导电微支架涂层(即氮掺杂碳纳米颗粒)的结合能够实现锌在表面-内部-空隙的次序沉积,能够显著提高锌负极的性能;
Smart Images

Figure CN117133889B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc anode materials for aqueous zinc-based batteries, specifically to a zinc anode with a carbon-supported metal single-atom functional coating, its preparation and application, and more specifically to a zinc anode material with a nitrogen-doped carbon-supported atomic-level Sn site coating, its preparation method and its application in aqueous zinc-ion batteries, zinc-air batteries, zinc-based flow batteries and other fields. Background Technology
[0002] The continuously growing global energy demand and the increasingly significant environmental pollution problems are two major challenges facing human society. Developing efficient, safe, low-carbon, and clean renewable energy sources is of great importance to achieving sustainable social development. Currently, the production, storage, transmission, and utilization of electricity rely on electrochemical energy conversion and storage devices of different specifications and types. Over the past thirty years, the rapid development and commercialization of lithium-ion batteries have been remarkable, bringing about an energy revolution in mobile electronic devices and electric vehicles. However, lithium-ion batteries are still limited by their relatively low specific capacity and cycle stability. Furthermore, because alkali metals (lithium, sodium, potassium, etc.) are highly sensitive to water and air, alkali metal-based batteries typically use organic electrolytes, which poses a risk of fire and explosion. Aqueous zinc-ion batteries possess a low redox potential (-0.762V vs. standard hydrogen electrode) and a high theoretical capacity (820mAh·g). -1 Zinc anodes (ZIBs) are currently a research hotspot in academia and industry due to their advantages such as high safety and abundant metal resources. However, they are still affected by the decline in discharge capacity and coulombic efficiency (CE) performance, caused by dendrite formation, electrode corrosion, and unfavorable side reactions of the zinc anode. The accumulation of zinc dendrites manifests as surface protrusions, exacerbating the roughness of the negative electrode surface, further leading to the formation of electrochemically inert "dead zinc," and even damaging the separator. In addition, the disordered morphology of the Zn anode leads to irregular electron distribution and high local current density, as well as the subsequent hydrogen evolution reaction (HER) at the interface. To address these issues and create a smoother zinc anode surface during cycling, numerous methods have been invested in optimizing the solid / liquid interface, including electrolyte additives, interface decorative layers, zinc-loving substrates, and electrode structure design. A major goal of dendrite and side reaction suppression is to achieve uniform Zn nucleation on the anode surface while preventing water molecule penetration. Therefore, creating abundant zinc-loving sites and constructing a hydrophobic interface layer are two key points for regulating the solid / liquid interface reaction. For establishing zinc-loving sites, the conventional approach is to design a zinc-loving host for Zn deposition. However, this increases electrode complexity, causes severe side reactions, and sometimes requires pre-depositing Zn. Common inorganic two-dimensional SEI layers cannot suppress the volume expansion of the Zn anode, and due to the Zn... 2+Diffusion is difficult, making deep cycling challenging. CN 110364732B discloses a composite zinc anode with an inorganic functional modification layer in an aqueous battery, its preparation method, and its application. However, this inorganic oxide artificial solid electrolyte interface (SEI) layer cannot provide a structured interface for adjusting the electric field distribution. CN 110416549 B discloses a metallic zinc anode with a uniform mesoporous structure coating, its preparation method, and its application. However, this type of coating cannot provide zinc-affinity sites, which is not conducive to the directional deposition / stripping of zinc.
[0003] Therefore, developing a zinc anode material that facilitates the directional deposition / stripping of zinc is of great practical significance. Summary of the Invention
[0004] Due to the aforementioned deficiencies in existing technologies, this invention provides a zinc anode material that facilitates the directional deposition / stripping of zinc, i.e., a high-performance zinc anode material. Specifically, it is a zinc anode material with an atomic-level Sn site coating supported by nitrogen-doped carbon, its preparation method, and its application in aqueous zinc-ion batteries, zinc-air batteries, zinc-based flow batteries, etc., overcoming the defects of existing zinc anode coating materials that are not conducive to the directional deposition / stripping of zinc.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A zinc anode with a carbon-supported metal single-atom functional coating includes a zinc foil substrate and a carbon-supported metal single-atom functional coating coated on the zinc foil substrate.
[0007] The carbon-supported metal single-atom functional coating includes carbon-supported single-atom metal particles and a binder. The carbon-supported single-atom metal particles include nitrogen-doped carbon nanoparticles and a metal-nitrogen-doped carbon layer coating the surface of the nitrogen-doped carbon nanoparticles. The metal in the metal-nitrogen-doped carbon layer is embedded in a single-atom manner.
[0008] Specifically, this invention involves loading a hydrophobic and zinc-loving three-dimensional functional coating onto the surface of a zinc anode. This coating guides the high-speed diffusion of zinc ions while effectively suppressing hydrogen evolution side reactions. The combination of atomic-level zinc-loving sites and the three-dimensional conductive microscaffold coating (i.e., nitrogen-doped carbon nanoparticles) enables the sequential deposition of zinc on the surface, inside, and in the voids, resulting in a long-life, high-performance dendrite-free zinc anode. This material facilitates the directional deposition / stripping of zinc and has promising application prospects.
[0009] As a preferred technical solution:
[0010] The zinc anode with a carbon-supported metal single-atom functional coating as described above, wherein the nitrogen-doped carbon nanoparticles are derived nitrogen-doped carbon obtained by calcining ZIF-8.
[0011] The present invention also provides a method for preparing a zinc anode with a carbon-supported metal single-atom functional coating as described above, comprising the following steps:
[0012] (1) Synthesize ZIF-8;
[0013] (2) Nitrogen-doped carbon nanoparticles were obtained by calcining ZIF-8;
[0014] (3) The metal ion precursor, hydrochloric acid dopamine solution and nitrogen-doped carbon nanoparticles were copolymerized and calcined to obtain nitrogen-doped carbon loaded with atomic-level metal sites.
[0015] (4) Nitrogen-doped carbon loaded with atomic-level metal sites and binder are dispersed in a solvent to prepare a dispersion;
[0016] (5) The dispersion is uniformly coated on the zinc foil surface and dried to obtain a zinc anode with a carbon-supported metal single-atom functional coating.
[0017] The above preparation method is simple, has good versatility, and can be applied to the preparation of different types of materials. It can easily achieve the preparation of large-area carbon-based nanomaterial coatings on the surface of zinc anodes and has good application prospects.
[0018] As a preferred technical solution:
[0019] In the preparation method described above, in steps (2) and (3), the calcination temperature is 800-1000℃, the calcination atmosphere is a hydrogen / argon mixture, the volume content of hydrogen in the hydrogen / argon mixture is 0-5%, and the calcination time is 1-3h.
[0020] In the preparation method described above, the metal ions in the metal ion precursor are selected from one or more of tin and bismuth, wherein the concentration of the metal ions is 1 to 3 mmol / L.
[0021] The concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 1–3 g / L;
[0022] The polymerization process takes 8 to 24 hours.
[0023] In the preparation method described above, the adhesive is selected from one or more of polyvinylidene fluoride and polytetrafluoroethylene;
[0024] The mass ratio of nitrogen-doped carbon to binder for the loaded atomic-level metal sites is 1 to 7:1.
[0025] In the preparation method described above, the coating specifically refers to coating using a 25-100 μm tetragonal coater.
[0026] The present invention also provides the application of a zinc anode with a carbon-supported metal single-atom functional coating as described above in zinc-based batteries (aqueous zinc-ion batteries, zinc-air batteries or zinc-based flow batteries).
[0027] In addition, the present invention also provides an aqueous zinc-ion battery, comprising a positive electrode, a zinc negative electrode, a separator, and an electrolyte;
[0028] The zinc negative electrode sheet is made using the zinc negative electrode as described above;
[0029] The zinc negative electrode and positive electrode are arranged opposite each other and separated by a separator, wherein the coated side of the zinc negative electrode faces the separator.
[0030] As a preferred technical solution:
[0031] In the aqueous zinc-ion battery described above, the positive electrode material is manganese dioxide;
[0032] The diaphragm is made of glass fiber;
[0033] The electrolyte is an aqueous solution of zinc sulfate, an aqueous solution of zinc trifluoromethanesulfonate, or an aqueous solution of zinc chloride. Of course, the zinc anode with a carbon-supported metal single-atom functional coating of the present invention is not only applicable to aqueous zinc-ion batteries, but also to other zinc-based batteries. This is merely one feasible technical solution of the present invention, and the scope of protection of the present invention is not limited thereto. Those skilled in the art can reasonably adjust the specific design according to actual needs.
[0034] Invention principle:
[0035] This invention uses a metal-organic framework-derived nitrogen-doped carbon material as a skeleton, and synthesizes atomic-level metal sites supported on nitrogen-doped carbon on the skeleton surface using in-situ polymerization and high-temperature calcination. This material is then coated onto a zinc sheet to obtain a zinc anode with a carbon-supported metal single-atom functional coating. The carbon-supported metal single-atom functional coating on the zinc anode has a hydrophobic / hydrophilic bilayer structure to guide the high-speed diffusion of zinc ions, while effectively suppressing hydrogen evolution side reactions. The combination of atomic-level zinc-loving sites and a three-dimensional conductive microscaffold coating enables sequential deposition of zinc on the surface, inside, and in the voids, achieving a long-life, high-performance dendrite-free zinc anode.
[0036] Specifically, the zinc-loving metal atoms at the interface of the carbon-supported metal single-atom functional coating can serve as nucleation sites to regulate zinc nucleation; the conductive carbon support helps achieve a uniform electric field distribution, thereby enabling nanoscale controlled uniform deposition of Zn; the hydrophobic / hydrophilic bilayer configuration creates a gradient distribution of electrolyte concentration, providing rapid Zn deposition. 2+The diffusion path enables directional deposition of zinc-affin metal atoms (NC) inside and on the surface; the three-dimensional structure coating enables surface-interior-interstitial deposition, thereby achieving a smooth electrode surface during deep cycling; the hydrophobic surface formed by the polydopamine-derived zinc-affin metal atom (NC) layer can reduce water molecule penetration, inhibit water decomposition at the interface, and minimize the generation of hydrogen evolution reaction and the formation of byproducts.
[0037] The above invention has the following advantages or beneficial effects:
[0038] (1) The zinc anode with carbon-supported metal single-atom functional coating of the present invention can guide the high-speed diffusion of zinc ions by loading a hydrophobic and zinc-loving three-dimensional functional coating on the surface of the zinc anode, while effectively suppressing the hydrogen evolution side reaction. The combination of atomic-level zinc-loving sites and three-dimensional conductive microscaffold coating (i.e. nitrogen-doped carbon nanoparticles) can realize the sequential deposition of zinc on the surface-inside-pores, which can significantly improve the performance of the zinc anode.
[0039] (2) The preparation method of the present invention is simple, has good versatility, and can easily realize the preparation of a large-area functional coating on the surface of zinc anode;
[0040] (3) The zinc anode with carbon-supported metal single-atom functional coating of the present invention has broad application potential in the fields of aqueous zinc-ion batteries, zinc-air batteries, and zinc-based flow batteries, and has good application prospects. Attached Figure Description
[0041] The invention, its features, shape, and advantages will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings. Like reference numerals denote like parts throughout the drawings. The drawings are not drawn to scale; their focus is on illustrating the gist of the invention.
[0042] Figure 1 Electron microscope image of a nitrogen-doped carbon (SnNC) coating loaded with atomic-level Sn sites;
[0043] Figure 2 Cross-sectional electron microscope image of a nitrogen-doped carbon coating loaded with atomic-level Sn sites;
[0044] Figure 3 For 1mA·cm -2 and 0.5mAh·cm -2 Electron microscope image of zinc foil with SnNC-modified coating after 100 cycles;
[0045] Figure 4 The zinc foil with SnNC modified coating (Example 1), zinc foil with NC modified coating (Comparative Example 1), and zinc foil (blank example) in a symmetrical battery were subjected to 1 mA·cm-2 1mAh·cm -2 The following is a cycle curve;
[0046] Figure 5 The zinc foil with SnNC modified coating (Example 1), zinc foil with NC modified coating (Comparative Example 1), and zinc foil (blank example) in a symmetrical battery were subjected to 10 mA·cm⁻¹. -2 10mAh·cm -2 The following is a cycle curve;
[0047] Figure 6 Electron microscope image of zinc foil with SnNC-modified coating after symmetric cell testing;
[0048] Figure 7 Capacity and coulombic efficiency curves of full cells composed of zinc foil with SnNC modified coating (Example 1), zinc foil with NC modified coating (Comparative Example 1), and zinc foil (blank example) with MnO2 cathode. Detailed Implementation
[0049] The structure of the present invention will be further described below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the present invention.
[0050] Example 1
[0051] A method for preparing a zinc anode with a carbon-supported Sn single-atom functional coating includes the following steps:
[0052] (1) Dissolve 3 mmol zinc nitrate hexahydrate in 30 mL methanol to prepare solution A; dissolve 12 mmol 2-methylimidazole in 10 mL methanol to prepare solution B; pour solution A into solution B quickly under magnetic stirring; after stirring the solution continuously at 25 °C for 24 hours, collect the ZIF-8 product by centrifugation.
[0053] (2) ZIF-8 powder was calcined at 900°C for 2 hours at a heating rate of 5°C / min under a mixed atmosphere of 5% hydrogen / 95% argon to obtain nitrogen-doped carbon (NC) nanoparticles.
[0054] (3) 110 mg of the calcined product was ultrasonically dispersed in 20 mL of ethanol to form a suspension C; 20 mg of stannous chloride dihydrate and 55 mg of dopamine hydrochloride were dissolved in 20 mL of ethanol and 10 mL of water to form a solution D; solution D was added to suspension C under magnetic stirring, followed by 750 μL of ammonia water; the mixture was stirred at 25 °C for 12 hours, the powder was collected by centrifugation, and then calcined at 900 °C for 2 hours under a 5% hydrogen / 95% argon mixed atmosphere at a heating rate of 5 °C / min to obtain nitrogen-doped carbon (SnNC) loaded with atomic-level Sn sites.
[0055] (4) Polish commercial zinc foil with a thickness of 0.2 mm with 250 and 800 grit sandpaper respectively to remove the potential oxide layer on the surface of the zinc foil; disperse 20 mg of product and 20 mg of polyvinylidene fluoride in 1 mL of N-methyl-2-pyrrolidone and stir for 12 hours to make it uniformly dispersed.
[0056] (5) The mixture was coated onto a polished zinc foil using a 100nm coater and dried at 60°C for 2 hours to obtain a zinc anode with a carbon-supported Sn single-atom functional coating.
[0057] The zinc anode with a carbon-supported metal single-atom functional coating is prepared, including a zinc foil substrate and a carbon-supported Sn single-atom functional coating coated on the zinc foil substrate; the carbon-supported Sn single-atom functional coating includes carbon-supported single-atom Sn particles and polyvinylidene fluoride, the carbon-supported single-atom Sn particles include nitrogen-doped carbon nanoparticles and a Sn-nitrogen-doped carbon layer coated on the surface of the nitrogen-doped carbon nanoparticles, in which Sn is embedded in a single-atom manner.
[0058] Electron micrographs of a carbon-supported Sn single-atom functional coating on a zinc anode with a carbon-supported metal single-atom functional coating—a nitrogen-doped carbon (Sn NC) coating with atomic-level Sn sites and its cross-section, as shown in the figure. Figure 1 and 2 As shown, the Sn NC particles are uniform in size with a diameter of ~750 nm, and no obvious Sn nanoparticles were observed. The scanning electron microscope image of the cross section shows that the SnNC coating thickness on the zinc foil surface is ~15 μm.
[0059] Comparative Example 1
[0060] A method for preparing a zinc anode with an NC-modified coating includes the following steps:
[0061] (1) Dissolve 3 mmol zinc nitrate hexahydrate in 30 mL methanol to prepare solution A; dissolve 12 mmol 2-methylimidazole in 10 mL methanol to prepare solution B; pour solution A into solution B quickly under magnetic stirring; after stirring the solution continuously at 25 °C for 24 hours, collect the ZIF-8 product by centrifugation.
[0062] (2) ZIF-8 powder was calcined at 900°C for 2 hours at a heating rate of 5°C / min under a mixed atmosphere of 5% hydrogen / 95% argon to obtain nitrogen-doped carbon (NC) nanoparticles.
[0063] (3) Use 250 and 800 grit sandpaper to polish 0.2 mm thick commercial zinc foil to remove the potential oxide layer on the surface of the zinc foil; disperse 20 mg nitrogen-doped carbon (NC) nanoparticles and 20 mg polyvinylidene fluoride in 1 mL N-methyl-2-pyrrolidone and stir for 12 hours to make it uniformly dispersed.
[0064] (4) The mixture was coated onto polished zinc foil using a 100μm coater and dried at 60°C for 2 hours to obtain a zinc anode with NC modified coating.
[0065] The zinc anode with a carbon-supported Sn single-atom functional coating prepared in Example 1, the zinc anode with an NC-modified coating prepared in Comparative Example 1, and the polished zinc foil (i.e. blank example) in step (5) of Example 1 were used as anode sheets to assemble a full cell. The parameters of the full cell are as follows: including a positive electrode sheet, a zinc anode sheet, a separator and an electrolyte. The zinc anode sheet and the positive electrode sheet are arranged opposite each other and separated by a separator. The coated side of the zinc anode sheet faces the separator. The positive electrode sheet is a manganese dioxide sheet. The separator is glass fiber. The electrolyte is an aqueous solution of zinc sulfate.
[0066] The above batteries were subjected to relevant tests, and the test results are as follows: Figures 4-5 and Figure 7 As shown, in the 1000-hour stability test of symmetrical cells, the Sn NC / Zn symmetrical cell exhibited stability at 1 mA cm⁻¹. -2 and 1mAh cm -2 It exhibits a stable low overpotential of approximately 23.8 mV. Figure 4 Illustrations (i)-(iii) show detailed potential curves for 40–46 hours, 500–506 hours, and 900–906 hours, with SnNC / Zn maintaining a low overpotential of 24.1 mV even after 900 hours. In contrast, symmetrical cells based on NC / Zn and Zn fail around 550 hours and 50 hours, respectively. Even at 10 mA cm⁻¹ -2 High cycling current density and 10mAh cm -2 Under deep cycling capacity ( Figure 5 SnNC / Zn-based symmetric cells can still maintain stable operation for 280 hours. Figure 7 The long-term cycling performance of the full cell is shown; the SnNC / Zn / / MnO2 cell can maintain 2Ag after 2800 cycles. -1 It maintained 76.2 mAh g at a current density. -1 The high capacity of the Zn-based cell, while maintaining a stable coulombic efficiency of ~100%, contrasts sharply with the extremely high degradation of NC / Zn and Zn-based full cells, resulting in poor device lifespan.
[0067] Electron microscope images of a full cell assembled using the zinc anode with a carbon-supported Sn single-atom functional coating prepared in Example 1 as the anode sheet after testing are shown below. Figure 6 As shown, Sn / NC Zn exhibits a smooth and flat electrode surface after cycling, proving that nanoscale scaling in Zn deposition does not cause surface protrusions or dendrite growth during long-term deposition / stripping cycles.
[0068] A full cell assembled using the zinc anode with a carbon-supported Sn single-atom functional coating prepared in Example 1 as the anode sheet, at 1 mA·cm -2 and 0.5mAh·cm -2 Electron microscope image of the negative electrode after 100 cycles as shown below Figure 3 As shown, on the SnNC / Zn anode surface, Zn is uniformly deposited on the SnNC surface in the form of ultra-small nanosheets. This is because SnNC has abundant Sn atomic sites and conductive carbon-based nanostructures, which is conducive to the uniform deposition of Zn and can avoid electrode surface deformation.
[0069] Example 2
[0070] A method for preparing a zinc anode with a carbon-supported Sn single-atom functional coating includes the following steps:
[0071] (1) Dissolve 3 mmol zinc nitrate hexahydrate in 30 mL methanol to prepare solution A; dissolve 12 mmol 2-methylimidazole in 10 mL methanol to prepare solution B; pour solution A into solution B quickly under magnetic stirring; after stirring the solution continuously at 25 °C for 24 hours, collect the ZIF-8 product by centrifugation.
[0072] (2) ZIF-8 powder was calcined at 900°C for 2 hours at a heating rate of 5°C / min under a mixed atmosphere of 5% hydrogen / 95% argon to obtain nitrogen-doped carbon (NC) nanoparticles.
[0073] (3) 110 mg of the calcined product was ultrasonically dispersed in 20 mL of ethanol to form a suspension C; 12 mg of stannous chloride dihydrate and 90 mg of dopamine hydrochloride were dissolved in 20 mL of ethanol and 10 mL of water to form a solution D; solution D was added to suspension C under magnetic stirring, followed by 750 μL of ammonia water; the mixture was stirred at 25 °C for 24 hours, the powder was collected by centrifugation, and then calcined at 900 °C for 2 hours under a 5% hydrogen / 95% argon mixed atmosphere at a heating rate of 5 °C / min to obtain nitrogen-doped carbon (SnNC) loaded with atomic-level Sn sites.
[0074] (4) Polish commercial zinc foil with a thickness of 0.2 mm with 250 and 800 grit sandpaper respectively to remove the potential oxide layer on the surface of the zinc foil; disperse 140 mg of product and 20 mg of polyvinylidene fluoride in 1 mL of N-methyl-2-pyrrolidone and stir for 12 hours to make it uniformly dispersed.
[0075] (5) The mixture was coated onto a polished zinc foil using a 25μm coater and dried at 60°C for 2 hours to obtain a zinc anode with a carbon-supported Sn single-atom functional coating.
[0076] Example 3
[0077] A method for preparing a zinc anode with a carbon-supported Bi single-atom functional coating includes the following steps:
[0078] (1) Dissolve 3 mmol zinc nitrate hexahydrate in 30 mL methanol to prepare solution A; dissolve 12 mmol 2-methylimidazole in 10 mL methanol to prepare solution B; pour solution A into solution B quickly under magnetic stirring; after stirring the solution continuously at 25 °C for 24 hours, collect the ZIF-8 product by centrifugation.
[0079] (2) ZIF-8 powder was calcined at 900°C for 2 hours at a heating rate of 5°C / min under a mixed atmosphere of 5% hydrogen / 95% argon to obtain nitrogen-doped carbon (NC) nanoparticles.
[0080] (3) 110 mg of the calcined product was ultrasonically dispersed in 20 mL of ethanol to form a suspension C; 17 mg of bismuth chloride and 55 mg of dopamine hydrochloride were dissolved in 20 mL of ethanol and 10 mL of water to form a solution D; solution D was added to suspension C under magnetic stirring, and then 750 μL of ammonia was added to the mixture; the mixture was stirred at 25 °C for 12 hours, the powder was collected by centrifugation, and then calcined at 900 °C for 2 hours under a 5% hydrogen / 95% argon mixed atmosphere at a heating rate of 5 °C / min to obtain nitrogen-doped carbon (Bi NC) loaded with atomic-level Bi sites.
[0081] (4) Polish commercial zinc foil with a thickness of 0.2 mm with 250 and 800 grit sandpaper respectively to remove the potential oxide layer on the surface of the zinc foil; disperse 20 mg of product and 20 mg of polyvinylidene fluoride in 1 mL of N-methyl-2-pyrrolidone and stir for 12 hours to make it uniformly dispersed.
[0082] (5) The mixture was coated onto polished zinc foil using a 100μm coater and dried at 60°C for 2 hours to obtain a zinc anode with a carbon-supported Bi single-atom functional coating.
[0083] Example 4
[0084] A method for preparing a zinc anode with a carbon-supported Bi single-atom functional coating includes the following steps:
[0085] (1) Dissolve 3 mmol zinc nitrate hexahydrate in 30 mL methanol to prepare solution A; dissolve 12 mmol 2-methylimidazole in 10 mL methanol to prepare solution B; pour solution A into solution B quickly under magnetic stirring; after stirring the solution continuously at 25 °C for 24 hours, collect the ZIF-8 product by centrifugation.
[0086] (2) ZIF-8 powder was calcined at 900°C for 2 hours at a heating rate of 5°C / min under a mixed atmosphere of 5% hydrogen / 95% argon to obtain nitrogen-doped carbon (NC) nanoparticles.
[0087] (3) 110 mg of the calcined product was ultrasonically dispersed in 20 mL of ethanol to form a suspension C; 28 mg of stannous chloride dihydrate and 30 mg of dopamine hydrochloride were dissolved in 20 mL of ethanol and 10 mL of water to form a solution D; solution D was added to suspension C under magnetic stirring, followed by 750 μL of ammonia water; the mixture was stirred at 25 °C for 8 hours, the powder was collected by centrifugation, and then calcined at 900 °C for 2 hours under a 5% hydrogen / 95% argon mixed atmosphere at a heating rate of 5 °C / min to obtain nitrogen-doped carbon (Bi NC) loaded with atomic-level Bi sites.
[0088] (4) Polish commercial zinc foil with a thickness of 0.2 mm with 250 and 800 grit sandpaper respectively to remove the potential oxide layer on the surface of the zinc foil; disperse 140 mg of product and 20 mg of polyvinylidene fluoride in 1 mL of N-methyl-2-pyrrolidone and stir for 12 hours to make it uniformly dispersed.
[0089] (5) The mixture was coated onto a polished zinc foil using a 50μm coater and dried at 60°C for 2 hours to obtain a zinc anode with a carbon-supported Bi single-atom functional coating.
[0090] Those skilled in the art should understand that variations can be implemented by combining existing technology with the above embodiments, which will not be elaborated here. Such variations do not affect the essence of the present invention, and will not be elaborated here either.
[0091] The preferred embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and the devices and structures not described in detail should be understood as being implemented in a conventional manner in the art. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention using the methods and techniques disclosed above, or modify them into equivalent embodiments with equivalent changes, without departing from the scope of the present invention. This does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the present invention's technical solutions still fall within the protection scope of the present invention.
Claims
1. A zinc anode with a carbon-supported metal single-atom functional coating, characterized in that: Includes a zinc foil substrate and a carbon-supported metal single-atom functional coating applied to the zinc foil substrate; The carbon-supported metal single-atom functional coating comprises carbon-supported single-atom metal particles and a binder. The carbon-supported single-atom metal particles include nitrogen-doped carbon nanoparticles and a metal-nitrogen-doped carbon layer coating the surface of the nitrogen-doped carbon nanoparticles. The metal in the metal-nitrogen-doped carbon layer is embedded in a single-atom manner. The metal is one or more of tin and bismuth.
2. The zinc anode with a carbon-supported metal single-atom functional coating according to claim 1, characterized in that, The nitrogen-doped carbon nanoparticles are derived nitrogen-doped carbon obtained by calcining ZIF-8.
3. A method for preparing a zinc anode with a carbon-supported metal single-atom functional coating as described in any one of claims 1 to 2, characterized in that, Includes the following steps: (1) Synthesis of ZIF-8; (2) Nitrogen-doped carbon nanoparticles were obtained by calcining ZIF-8; (3) The metal ion precursor, hydrochloric acid dopamine solution and nitrogen-doped carbon nanoparticles were copolymerized and calcined to obtain nitrogen-doped carbon loaded with atomic-level metal sites. (4) Nitrogen-doped carbon loaded with atomic-level metal sites and binder are dispersed in a solvent to prepare a dispersion; (5) The dispersion is evenly coated on the surface of zinc foil and dried to obtain a zinc anode with a carbon-supported metal single-atom functional coating.
4. The preparation method according to claim 3, characterized in that, In steps (2) and (3), the calcination temperature is 800~1000℃, the calcination atmosphere is a hydrogen / argon mixture, the volume content of hydrogen in the hydrogen / argon mixture is 0~5%, and the calcination time is 1~3h.
5. The preparation method according to claim 3, characterized in that, The metal ions in the metal ion precursor are selected from one or more of tin and bismuth, wherein the concentration of the metal ions is 1~3 mmol / L; The concentration of dopamine hydrochloride in the dopamine hydrochloride solution is 1~3 g / L; The polymerization process takes 8 to 24 hours.
6. The preparation method according to claim 3, characterized in that, The adhesive is selected from one or more of polyvinylidene fluoride and polytetrafluoroethylene; The mass ratio of nitrogen-doped carbon to binder for the loaded atomic-level metal sites is 1 to 7:
1.
7. The preparation method according to claim 3, characterized in that, The coating specifically refers to coating using a 25~100μm tetrahedral coater.
8. The application of a zinc anode with a carbon-supported metal single-atom functional coating as described in any one of claims 1 to 2 in zinc-based batteries.
9. An aqueous zinc-ion battery, characterized in that, Includes positive electrode, zinc negative electrode, separator and electrolyte; The zinc negative electrode sheet is prepared using the zinc negative electrode as described in any one of claims 1 to 2; The zinc negative electrode and positive electrode are arranged opposite each other and separated by a separator, wherein the coated side of the zinc negative electrode faces the separator.
10. An aqueous zinc-ion battery according to claim 9, characterized in that, The positive electrode is made of manganese dioxide. The diaphragm is made of glass fiber; The electrolyte is an aqueous solution of zinc sulfate, an aqueous solution of zinc trifluoromethanesulfonate, or an aqueous solution of zinc chloride.
Citation Information
Patent Citations
A composite zinc anode with an inorganic functional modification layer in an aqueous battery, its preparation method and application
CN110364732B
A zinc anode with a uniform mesoporous coating, its preparation method and application
CN110416549B
Composite negative electrode material and secondary battery thereof
CN105406076A
Nanoparticle-compounded ZIF-8 negative electrode material of high specific capacity bismuth as well as preparation method and application of nanoparticle-compounded ZIF-8 negative electrode material
CN108832110A